Rediseño Arquitectónico de la Plaza San Blas en la Parroquia Urbana Pelileo Grande. - Pérez Pérez, Allison Katheryne (2024)
Currently, the Pelileo canton has seen demographic growth that has caused an accelerated urbanization process, which is why public spaces are no longer a priority. In addition, different infrastructures are in deterioration or obsolete, due to the years and the need to adapt to said urban growth. Plaza San Blas has been an important wholesale trade space at the cantonal level for two decades, however, the increase in stallholders has caused the space to be collapsed and the authorities have found it necessary to relocate it. Given this, the total abandonment of the square would generate an underuse of the space as has been evidenced by the days in which it is not sold. Based on the problems identified, it is imperative to give said space a new use. The objective of the project lies in analyzing the needs of the population based on visits and on-site work, in such a way as to generate strategies applied to the design that allow the revitalization, connection and transformation of the area, from an urban architectural intervention that seeks to integrate the inhabitants with space. In addition, a participatory design is promoted, so that people feel involved in decision-making, which allows creating a sense of belonging and appropriation of the inhabitants, trying to convert them into spaces that are part of the daily lives of the inhabitants. The proposed areas are designed to generate interaction with different integrated elements to achieve greater vitality in the public space.